2020
DOI: 10.3390/w12071961
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling Hypoxia Occurrence in Estuaries, Chester River, Chesapeake Bay

Abstract: The Chester River, a tributary of Chesapeake Bay, provides critical habitats for numerous living species and oyster aquaculture, but faces increasing anthropogenic stresses due to excessive nutrient loading and hypoxia occurrence. An application of the Integrated Compartment Water Quality Model (ICM), coupled with the Finite-Volume Community Ocean Model (FVCOM), was carried out to study the controlling mechanisms and interannual variability in hypoxia occurrence from 2002 to 2011. Our study shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The ratio of phosphorus (PO 4 ), nitrogen (NO 23 + NH 4 ), and silica concentrations to their respective half-saturation coefficients indicated that at both the upstream and downstream stations, none of the above nutrients were limiting, except for phosphorus during a brief period during winter-spring (i.e., ratios >1, data not shown), during which GPP was reduced by PO 4 load reductions scenarios (Figure 10). Tian (2020) recently reported that nutrient loading was an important factor controlling hypoxia in the Chester River using a multi-year numerical model simulation, but the reported half-saturation coefficients for nitrogen and phosphorus uptake (0.5 mg N L −1 and 0.0025 mg P L −1 ) were much larger than those used in the other Chesapeake water quality models (e.g., 0.007-0.025 mg N L −1 ) Feng et al 2015;Cerco and Noel 2017). This clearly indicates that modest alterations in nutrient loading rates may be expected to have a much more limited impact on phytoplankton growth and hypoxia than the mainstem Chesapeake Bay and other nutrient-limited estuaries.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of phosphorus (PO 4 ), nitrogen (NO 23 + NH 4 ), and silica concentrations to their respective half-saturation coefficients indicated that at both the upstream and downstream stations, none of the above nutrients were limiting, except for phosphorus during a brief period during winter-spring (i.e., ratios >1, data not shown), during which GPP was reduced by PO 4 load reductions scenarios (Figure 10). Tian (2020) recently reported that nutrient loading was an important factor controlling hypoxia in the Chester River using a multi-year numerical model simulation, but the reported half-saturation coefficients for nitrogen and phosphorus uptake (0.5 mg N L −1 and 0.0025 mg P L −1 ) were much larger than those used in the other Chesapeake water quality models (e.g., 0.007-0.025 mg N L −1 ) Feng et al 2015;Cerco and Noel 2017). This clearly indicates that modest alterations in nutrient loading rates may be expected to have a much more limited impact on phytoplankton growth and hypoxia than the mainstem Chesapeake Bay and other nutrient-limited estuaries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Li et al (2016) concluded that variability in N load is the main driver of interannual variability of hypoxia in the Bay. On a more local scale, Tian (2020) reported that nutrient loads determine the intensity and variability in hypoxia in the Chester River estuary.…”
Section: Estuarine Response To Changes In Nutrient Loadsmentioning
confidence: 99%
“…These heterogeneous conditions emerge from strong spatial patterns of phytoplankton biomass, as well as interactions between the coastline and current that drive changes in current velocity and direction. For example, Tian (2019) and Tian (2020) found that interactions between physics and coastline meanders can generate complex advection features that fundamentally alter biogeochemical processes and water quality properties in the Chester River. Helical advection resulting from interactions between currents and the coastline can interrupt saltwater intrusion, vertical diffusivity, Classification And Regression Tree (CART) analysis of DO simulation time-series data at the upper estuary station XHH3851.…”
Section: Physical Impacts On Do Variabilitymentioning
confidence: 99%